1992
DOI: 10.1073/pnas.89.20.9969
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, genetic mapping, and expression analysis of an Arabidopsis thaliana gene that encodes 1-aminocyclopropane-1-carboxylate synthase.

Abstract: A genomic clone of one member of the Arabidopsis thaliana (L.) Heynh. 1-aminocyclopropane-1-carboxylate (ACC) synthase (S-adenosyl-L-methionine methylthioadenosine-lyase, EC 4.4.1.14) gene family (AT-ACC1) was isolated and sequenced. A region of homology was found in the 5'-untranslated region with the promoter of a zucchini and a tomato ACC synthase gene. Comparison of its primary structure with other ACC synthases revealed conservation of seven peptide regions as well as similarity with 11 amino acids of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
55
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 30 publications
(22 reference statements)
2
55
0
Order By: Relevance
“…It has been hypothesized that this change is a direct consequence of a change in the orientation of microtubules. This has been supported in part by the observation that a net reorientation of microtubules in the longitudinal direction is a consequence of ethylene treatment (Raskin, 1991).In this paper, we report on the developmental regulation of a member of the Arabidopsis ACC synthase gene family, ACSl (previously referred to as AMCC7 by Van Der Straeten et al [1992] or ACCP by Liang et al [1992], respectively). The promoter-fbglucuronidase (gus) fusion technique (Jefferson, 1987;Jefferson et al, 1987) has been used to study the expression of ACS7.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…It has been hypothesized that this change is a direct consequence of a change in the orientation of microtubules. This has been supported in part by the observation that a net reorientation of microtubules in the longitudinal direction is a consequence of ethylene treatment (Raskin, 1991).In this paper, we report on the developmental regulation of a member of the Arabidopsis ACC synthase gene family, ACSl (previously referred to as AMCC7 by Van Der Straeten et al [1992] or ACCP by Liang et al [1992], respectively). The promoter-fbglucuronidase (gus) fusion technique (Jefferson, 1987;Jefferson et al, 1987) has been used to study the expression of ACS7.…”
mentioning
confidence: 72%
“…The main focus has been on the regulation of ACC synthase gene expression because of its key regulatory role in the pathway. This implies that diverse inducers of ethylene production are also inducers of de novo synthesis of ACC synthase (Yang and Hoffmann, 1984; Van Der Straeten and Van Montagu, 1991).ACC synthases have been cloned from tomato (Van Der Straeten et al, 1990; Olson et al, 1991; To whom correspondence should be addressed.Yip et al, 1992), winter squash (Nakajima et al, 1990), zucchini (Huang et al, 1991), Arabidopsis (Liang et al, 1992; Van Der Straeten et al, 1992), mung bean (Botellaet al, 1992; Kim et al, 1992), carnation (Park et al, 1992), orchid (ONeill et al., 1993), tobacco (Bailey et al, 1992), and apple (Dong et ai., 1991; Kim et al, 1992). In several cases, it has been shown that ACC synthase genes belong to a multigene family and that they are differentially responsive to various ethyleneinducing factors and conditions such as wounding, fruit ripening, and auxins, although in certain cases some leve1 of coordination was demonstrated (Nakajima et al, 1990; Van Der Straeten et al, 1990; Dong et al, 1991; Olson et al, 1991; ; Yip et ai., 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Highly divergent ACC synthase multigene families have been identified and characterized in Arabidopsis (Liang et al, 1992(Liang et al, , 1996; Van der Straeten et al, 1992), tomato (Olson et al, 1991;Rottmann et al, 1991;Yip et al, 1992;Lincoln et al, 1993;Oetiker et al, 1997), mung bean (Botella et al, 1992a(Botella et al, , 1992b(Botella et al, , 1993Kim et al, 1992Kim et al, , 1997, zucchini (Huang et al, 1991), rice (Zarembinski and Theologis, 1993), potato (Destefano-Beltran et al, 1995;Schlagnhaufer et al, 1995), and orchid (Bui and O'Neill, 1998). The Arabidopsis gene family includes at least five members whose expression is differentially induced by hormones, developmental cues, Li ϩ , and the protein-synthesis inhibitor CHX (Liang et al, 1996).…”
mentioning
confidence: 99%
“…In this pathway, the rate-limiting step is the conversion of S-AdoMet to ACC. In Arabidopsis, seven ACS genes have been characterized, and their transcription is differentially regulated during development and in response to stressful stimuli (Liang et al, 1992;Van der Straeten et al, 1992;Arteca and Arteca, 1999;Lin et al, 2009).…”
Section: Ethylenementioning
confidence: 99%